2020
DOI: 10.3390/ijms21114173
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Scaffold Stimulates Differentiation and Proangiogenic Activities of Myogenic Progenitor Cells

Abstract: The physiological process of muscle regeneration is quite limited due to low satellite cell quantity and also the inability to regenerate and reconstruct niche tissue. The purpose of the study was to examine whether a graphene oxide scaffold is able to stimulate myogenic progenitor cell proliferation and the endocrine functions of differentiating cells, and therefore, their active participation in the construction of muscle tissue. Studies were carried out using mesenchymal cells taken from 6-day-old chicken e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Low cytotoxicity and the interactive surface of graphene oxides create promising possibilities for use in drug delivery platforms. In some of the previous experiments, graphene oxide used as a scaffold stimulated the growth of some cells and inhibited other cells (cell cultures of different origin from chicken embryos) [ 50 , 51 ]. In other studies, it was demonstrated that graphene was up taken by cells [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low cytotoxicity and the interactive surface of graphene oxides create promising possibilities for use in drug delivery platforms. In some of the previous experiments, graphene oxide used as a scaffold stimulated the growth of some cells and inhibited other cells (cell cultures of different origin from chicken embryos) [ 50 , 51 ]. In other studies, it was demonstrated that graphene was up taken by cells [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that graphene derivatives promote myogenic differentiation of several progenitors and stem cells, including MSC. Mateusz et al demonstrated GO-induced MyoD upregulation and proangiogenic activities of myogenic progenitor cells . The other study indicated that graphene form accelerated myofibroblast differentiation of bone marrow derived MSC in the presence of differentiation medium by upregulation of TGF-β1 .…”
mentioning
confidence: 96%
“…Excessive graphene oxide hindered angiogenesis of human endothelial cells by altering the distribution of mitochondria and disturbing several metabolic pathways. Contrary to in vitro results, in vivo data showed that 2D nanomaterials stimulate the formation new vessels in different disease models (Qian et al, 2019d;Norahan et al, 2019;Wierzbicki et al, 2020). One possible explanation for this phenomenon could be that in vivo studies utilized scaffolds which allow for the controlled release of 2D nanomaterials.…”
Section: D Nanomaterials Facilitate Micro-vessel Formation and Provide Guidance For Migrating Schwann Cellsmentioning
confidence: 75%